In-Silico Study: Potential Inhibitor of Cyclin-Dependent Kinase 6 (CDK6) from Natural Plant Compounds for Melanoma Treatment - Putri Aliya Ahadini; Adhyatma Ismu Reihan; Muhamad Bagus Wira Utama; Siti Khaerunnisa; Fadilah Fadilah (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2022)
Highlights:1. Melanoma is the most aggressive and dangerous type of skin cancer. 2. Cyclin-dependent kinase 6 (CDK6) had a role in melanoma progression.3. Chlorogenic acid, guattegaumerine, luteolin, and acronycine were potential natural compounds in plants as CDK6 inhibitors. AbstractIntroduction: Melanoma is the most aggressive and dangerous type of skin cancer. It usually occurs in the skin because melanocytes originate from the neural crest cells that migrate. A previous study stated misregulation of cyclin-dependent kinase 6 (CDK6) had a role in melanoma progression. This study aimed to identify the potential natural compound targeting and modulating the CDK6.Methods: This was an investigative study using in-silico docking analysis to search for compatible ligands and potential inhibitors to CDK6 protein. This study screened 46 natural compounds based on the drug-likeliness based on Lipinski’s rules of five and used PyRx (AutoDock Vina) software for the initial screening. 10 compounds with the highest binding energy underwent docking simulation using Molecular Operating Environment (MOE) software.Results: Chlorogenic acid, guattegaumerine, luteolin, and acronycine were potential natural compounds in plants as CDK6 inhibitors.Conclusion: This study found that chlorogenic acid was the most potential to be an inhibitor of CDK6 compared to other compounds screened.